Using control-value theory to predict completion intentions in vocational education students. (4th May 2019) - Hutton, E. A.; Skues, J. L.; Wise, L. Z.
ABSTRACT: This study used Control-Value Theory to examine the extent to which appraisals of control and value predicted students' intentions to complete their studies and whether the effects of these appraisals on completion intentions are mediated by the achievement emotions of enjoyment, frustration, anger and boredom. A sample of 158 Australian vocational education students completed a survey measuring control, value, achievement emotions and intentions to complete. Structural Equation Modelling revealed that both higher levels of control and higher levels of value predicted intentions to complete, though no support was found for an interaction between control and value in predicting completion intentions. Contrary to expectations, no support was found for achievement emotions mediating the relationships between both control and value and intentions to complete. It was concluded that subjective control and value may act as protective resources for students in maintaining their intentions to complete their studies.